THE EVOLUTION OF ASSET MARKETS IN UZBEKISTAN: EXPLORE THE HISTORICAL DEVELOPMENT OF FINANCIAL MARKETS IN UZBEKISTAN, FOCUSING ON KEY REFORMS AND THEIR IMPACT ON MARKET EFFICIENCY AND ACCESSIBILITY - Jo’rayev Og’abek (European Science Publishing, 2024)
Uzbekistan, a Central Asian country with a rich history, has undergone significant economic transformations in recent decades. One of the most notable developments has been the evolution of its asset markets, which have played a crucial role in shaping the country's financial landscape. This article aims to chronicle the transformation of Uzbekistan's asset markets, highlighting the key milestones, driving forces, and challenges that have shaped their growth.
Keywords: financial market, economic ways, developing system, financial barriers, recent reforms.